1998
DOI: 10.1016/s0736-4679(98)80045-0
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle crashes and maternal mortality in New Mexico: the significance of seat belt use

Abstract: In recent years, as deaths from medical complications during pregnancy have declined, injuriesspecifically those sustained in motor vehicle crashes-represent a growing proportion of all pregnancy-associated deaths. To investigate pregnancy-associated deaths in motor vehicle crashes in New Mexico, we scrutinized the database of the New Mexico Office of the Medical Investigator for all deaths during pregnancy and up to 6 weeks postpartum from 1986 through 1995. A total of 97 deaths were identified, 47 of which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…These incidents have occurred during pregnancy, in the second trimester of pregnancy, or even at term or when the mother was lactating. 25 A collection of 51 pregnant women with burns (27.45% self-inflicted, 72.55% unintentional) in a 9-year prospective study found burns were usually the result of kerosene ignition (68.6% of all patients, 100% of self-inflicted patients) resulting in 20 deaths from burns exceeding 40% of the surface area. Thirteen of these were self-inflicted.…”
Section: Discussionmentioning
confidence: 99%
“…These incidents have occurred during pregnancy, in the second trimester of pregnancy, or even at term or when the mother was lactating. 25 A collection of 51 pregnant women with burns (27.45% self-inflicted, 72.55% unintentional) in a 9-year prospective study found burns were usually the result of kerosene ignition (68.6% of all patients, 100% of self-inflicted patients) resulting in 20 deaths from burns exceeding 40% of the surface area. Thirteen of these were self-inflicted.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] We found that the injury fatality rate contributed more to the difference in fatal crash incidence density than either crash injury rate or crash incidence density. Since the fatal crash incidence density and the crash incidence density both correct for vehicle miles traveled (driving exposure), the increased risk for fatality on a rural road is linked with factors associated with the crash and after the crash rather than with driving exposure.…”
Section: Discussionmentioning
confidence: 99%
“…4 15 According to the 2001 National Highway Traffic Safety Administration (NHTSA) traffic safety statistics, 61% of traffic fatalities occurred in rural areas even though rural areas account for only 40% of the vehicle miles traveled and 21% of the population. 19 Rural motor vehicle injury fatality rates have been higher than urban rates in several state and local studies, [6][7][8][9][10][11][12][13][14][15][16][17] as well as in studies of different countries. 18 20-23 Although motor vehicle injury fatality rates have declined over the last 20 years, rural rates continue to exceed urban rates.…”
mentioning
confidence: 99%
“…In New Mexico, Schiff et al (1997) 19 examined maternal death records between 1986 and 1995 and found that motor vehicle crashes accounted for 70% of all injury-related maternal deaths. 19 Among these deaths, 77% of the women were not wearing seat belts at the time of the crash.…”
Section: Motor Vehicle Crashes and Maternal Outcomesmentioning
confidence: 99%
“…In New Mexico, Schiff et al (1997) 19 examined maternal death records between 1986 and 1995 and found that motor vehicle crashes accounted for 70% of all injury-related maternal deaths. 19 Among these deaths, 77% of the women were not wearing seat belts at the time of the crash. A second study conducted by Schiff et al (2005) 15 in Washington State described the types of injuries sustained by pregnant women who were hospitalized following a motor vehicle crash.…”
Section: Motor Vehicle Crashes and Maternal Outcomesmentioning
confidence: 99%